Penerapan Model Problem Based Learning Terhadap Hasil Belajar Siswa Kelas XI IPS di SMAN 8 Kendari Pada Materi Pokok Ketahanan Pangan, Industri dan Energi - Sitti Nuraeni; La Harudu; La Ode Nursalam; Surdin Surdin (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Senior High School 8 Kendari is one of the schools in Nambo Village, Nambo District, where students are less active in Geography learning. This is because the learning methods teachers use are still conventional. This study aims to determine the effect of the Problem-Based Learning model on the learning outcomes of class XI IPS students on the material of Food Security, Industry, and Energy. This research was conducted at Senior High School 8 Kendari in class XI. The method used was an experiment with a pre-test and post-test control group design. This study used two sample groups, namely, the experimental group and the control group. The data were analyzed using descriptive analysis and inferential analysis. Based on the data analysis, the following conclusions were obtained: 1) there is no significant difference in the average pre-test scores of students in the experimental class and the control class with the results of the t-test showing that the t- statistics = 0.06 <2.00 at ɑ = 0.05; 2) The average post-test score of the experimental class was significantly better than the average post-test score of the control class, with the t-test results showing that t- statistics = 2.31 > t-table = 2.00 at ɑ = 0.05.